New Wood Products in our Future Economy - Trayer, Geo. W. (Indian Forester, 1946)
This paper deals chiefly with two groups of new wood produots-(I) those in which the wood has been modified by mechanical or physical means, and (2) those in which the wood has been converted by chemicals or heat into some enitrely different form. The author believes that these new products will supplement rather than replace such standard products as lumber, veneer, and pulp and stresses the dependence of all of the wood-using industries upon continuous, balanced production of the wood crop from managed forests.